Evaluasi Kesesuaian Penempatan Keramba Jaring Apung Pulau Gili Ketapang, Probolinggo - Ekavia Vinca Mulativa; Viv Djanat Prasita; Rudi Siap Bintoro (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2023)
The research aims to analyze or evaluate the suitability of placing Floating Net Cages on the island of Gili Ketapang using Hydro-Oceanographic parameters. The sampling method in this study used purposive sampling method in December 2022. After obtaining primary data and secondary data then the overlay process is carried out to determine the suitability of land for KJA. While the method used to analyze the results of the study using the scoring method. The type of tides on the island of Gili Ketapang is mixed double daily, the greatest current velocity value of 0.3-0.4 m / s in the transitional season 2, the highest waves in the west season with a height of 0.3-0.4 m. The results of research on several oceanographic parameters on Gili Ketapang Island can be concluded that the conditions on Gili Ketapang Island are categorized as feasible for grouper cultivation with Floating Net Cages.